2021
DOI: 10.1371/journal.pone.0258381
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone in Sri Lankan pregnant women: Vitamin D and other determinants

Abstract: Introduction Determinants of parathyroid hormone level during pregnancy have been less frequently studied. We aimed to describe the serum parathyroid hormone (PTH) and its determinants in Sri Lankan pregnant women in a community setting. Materials and methods In this cross-sectional analysis, 390 pregnant mothers in their third trimester were enrolled from primary care centers of 15 health divisions in the Colombo District in Sri Lanka. Venous blood was analyzed for a total 25-hydroxyvitamin-D [25(OH)D], ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Yet, vitamin D deficiency is high in all age groups [5,6]. The authors of this manuscript have previously reported high VDD rates among pregnant women in this population [7]. Thus, it can be assumed that living in a tropical country does not ensure adequate serum vitamin D. Factors such as season and latitude affect vitamin D production in the exposed skin.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Yet, vitamin D deficiency is high in all age groups [5,6]. The authors of this manuscript have previously reported high VDD rates among pregnant women in this population [7]. Thus, it can be assumed that living in a tropical country does not ensure adequate serum vitamin D. Factors such as season and latitude affect vitamin D production in the exposed skin.…”
Section: Introductionmentioning
confidence: 91%
“…This was part of a cross-sectional study of pregnant women from primary healthcare units in Western Sri Lanka from October 2018 to May 2019 [7]. In brief, pregnant mothers in the third trimester were enrolled using stratified random sampling according to the population proportions of primary health care units.…”
Section: Study Participantsmentioning
confidence: 99%
“…A través del deporte, los individuos aprenden a valorar las fortalezas y debilidades de cada miembro del equipo, trabajando juntos para lograr un objetivo común (Ferries, 2022). Además, el deporte proporciona un entorno donde se pueden practicar y mejorar habilidades de liderazgo y toma de decisiones en un contexto de equipo (Kaneshapillai, 2023).…”
Section: Trabajo En Equipo Y Cooperaciónunclassified